The Role of Nurses to Optimizing the Mechanical Ventilation for Acute Respiratory Failure in the Intensive Care Unit (ICU) of Hospital - Abd Hady Junaidi; Sri Angriani; Hariani Hariani; Masdiana AR; Muh Nur; Rahman Rahman (Direktorat Politeknik Kesehatan Makassar, 2025)
Background: The largest component at every health care facility center is the Nurse. In hospitals, nurses are placed in various health care units or sections, one of which is the Intensive Care Unit (ICU). Generally, Nurses at ICU have greater duties, roles, and responsibilities than nurses in other service units. Every day, these nurses must deal with critical patients, especially patients with acute respiratory failure on ventilators whose lives are threatened and have a high risk of death. Therefore, ICU nurses are increasingly required to play an integrated and comprehensive role to optimize mechanical ventilation management so that critical patients (acute respiratory failure) can be saved. Objective: To examine the nurse’s role of ICU and any supporting and inhibiting factors them to optimizing mechanical ventilation in patients with acute respiratory failure at the ICU. Method: A qualitative descriptive as type of this study, and use analytical, exploratory, phenomenological, and evaluative design. This research has been conducted in the ICU Room of Dr. Wahidin Sudirohusodo General Hospital of Makassar, Makassar City, South Sulawesi Province, Indonesia. The subjects are 21 nurses at ICU’s room. The informants include: the doctor in charge of the ICU, the Head of the Nursing Section, nurses, patients and families. Observation, interviews, and documentation as methods are used to collecting any data need to analyses problem and objective this study. A qualitative used as analyses approach.Results: All nurses at ICU room of hospital have an urgent, important and strategic role to optimizing mechanical ventilation against patients with acute respiratory failure. The specifically roles that must be played them by stages, integrated and holistic include: observation (observer), monitoring (monitor), evaluation of monitoring results and data analysis, airway management, examination and assessment of patient conditions, nursing care and actions, communication and coordination, preparedness and collaboration, as well as prevention and management of complications. The supporting factors of the role of nurses at ICU include: the human resources (HR) competence of nurses, the increasing number of acute respiratory failure patients requiring care, policy support and mechanisms as guidelines, support from hospital management, infrastructure and facilities and equipment, communication relationships and lines of coordination and collaboration, and the support of the patient's family. While the inhibiting factors include: patient factors, nurse negligence factors (in monitoring and managing ventilators, evaluating and analyzing data, managing patient breathing), quantity and quality of nurse HR factors, high nurse workload factors, limited time management factors in assessments, limited infrastructure and facilities and equipment factors. ineffective communication factors, conflict of interest factors, and poor role conflict management factors